2005
DOI: 10.1242/jeb.01451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological state, mass change and diet on plasma metabolite profiles in the western sandpiperCalidris mauri

Abstract: were negatively related to the rate of mass change (independent of diet), and butyrate was negatively related to the rate of mass change on both diets (though the slope of this relationship was diet dependent). Uric acid was positively related to the rate of mass change but only for birds on the low-fat diet. Our study therefore confirms that measurement of plasma metabolites can provide robust information on physiological state (gain, loss) and the rate of mass change (e.g. in free-living birds caught only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 28 publications
3
57
2
1
Order By: Relevance
“…Our results correspond with the findings in a previous long-term study on the Red Knot that found no correlation between triglyceride concentrations (samples taken immediately after capture) and body-mass change (Jenni-Eiermann et al 2002). In the Western Sandpiper, residuals of triglyceride (from the relationship with body mass) are also not correlated with bodymass change (calculated over a 2-day period; Seaman et al 2005). In an earlier study, however, residual triglyceride concentrations did correlate with short-term body-mass change but not with weekly body-mass change (Williams et al 1999).…”
Section: Triglyceridesmentioning
confidence: 82%
See 2 more Smart Citations
“…Our results correspond with the findings in a previous long-term study on the Red Knot that found no correlation between triglyceride concentrations (samples taken immediately after capture) and body-mass change (Jenni-Eiermann et al 2002). In the Western Sandpiper, residuals of triglyceride (from the relationship with body mass) are also not correlated with bodymass change (calculated over a 2-day period; Seaman et al 2005). In an earlier study, however, residual triglyceride concentrations did correlate with short-term body-mass change but not with weekly body-mass change (Williams et al 1999).…”
Section: Triglyceridesmentioning
confidence: 82%
“…Food (trout pellets, Trouvit Classic 2P, Skretting, Hendrix SpA, Italy; composition: crude protein 45%, carbohydrate 21%, crude fat 16%, crude ash 9%, lysine 3%, indigestible fibers 2%, phosphorus 1%) and fresh water were available ad libitum. This high-fat, high-protein diet was used in a previous study (JenniEiermann et al 2002) and resembles the standard diet used in comparable studies of captive Western Sandpipers (e.g., Williams et al 1999, Seaman et al 2005. As part of the birds' routine care, their body mass ( 1 g) was determined weekly.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of total proteins and triglycerides are often characteristic of short periods of food deprivation and covary with size-corrected body mass of birds (Boismenu et al 1992;Dawson and Bortolotti 1997;Guglielmo et al 2005). Also, plasma triglyceride concentrations have been widely used as indicators of mass gain and refuelling performance in shorebirds (Williams et al 1999;Seaman et al 2005).…”
Section: Plasma Protein and Triglyceridesmentioning
confidence: 99%
“…Some limited previous studies have reported on different hematology and serum biochemistry parameters of several amphibian species, including Rana esculenta (Sinha, 1983), rhacophorid frog (Mahapatra et al, 2012) and dubois's Tree Frog Polypedates teraiensis (Das and Mahapatra, 2014). Hematology and serum biochemistry parameters vary under different pathological, physiological, ecological and environmental conditions in animal population (Llacuna et al, 1996;Sarasola et al, 2004;Seaman et al, 2005). Amphibians are considered to be sensitive animals and show physiological variables to acute environmental changes (Carey, 2005).…”
Section: Introductionmentioning
confidence: 99%